2014
DOI: 10.1007/s13337-014-0239-3
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of foot and mouth disease in Karnataka state, India: a retrospective study

Abstract: A retrospective study on the epidemiology of foot and-mouth disease (FMD) in Karnataka, India between the years 1977 and 2012-13 based on the data collected through passive and active surveillance was undertaken. A total of 11,159 outbreaks with 0.271 million cases of FMD were recorded from 30 different revenue districts of Karnataka. There was a significant difference between the years for the annual incidence of FMD (P = \0.001, F = 19.10) and also between the months (P = \0.001, F = 4.22). Cattle and buffal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 11 publications
0
15
1
Order By: Relevance
“…On an average, outbreaks were recorded in 21 districts every year, of which only 10.8 outbreaks were confirmed [16]. Not all the clinically reported outbreaks could be confirmed in the present study as well.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…On an average, outbreaks were recorded in 21 districts every year, of which only 10.8 outbreaks were confirmed [16]. Not all the clinically reported outbreaks could be confirmed in the present study as well.…”
Section: Discussioncontrasting
confidence: 53%
“…Hence, it is not surprising that few districts may have higher prevalence of anti-NSP antibodies compared to others. Large numbers of outbreaks were reported from the dry zones and transition zones where the majority of the susceptible livestock population is located [16]. Before the implementation of vaccination programme, seroprevalence in these zones was more than 50 % which subsequently reduced to less than 25 % at the end of IV th phase of vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in India have also shown FMD outbreaks throughout the year, with a higher prevalence of outbreaks in the winter months (Bhat & Taneja ; Hegde et al . ). In contrast to the current study, a study in Bangladesh reported the highest incidence of FMD outbreaks during the post‐monsoon season (September‐November), followed by the pre‐monsoon season (March‐May), and winter (December‐February) (Kamaruddin & Pandit ).…”
Section: Discussionmentioning
confidence: 97%
“…For outbreak investigation, an animal was considered positive for FMD based on the clinical definition i.e. high body temperature, excessive salivation, vesicles formation on the tongue, nose, lips, oral mucosa, plus the inter-digital spaces and coronary bands on the feet, along with few or all signs of reduced appetite, depression, fever, hypersalivation, and lameness 36 , 58 – 60 .…”
Section: Methodsmentioning
confidence: 99%